(untitled) (Baghdad Science Journal, 2024)
Hydrochlorothiazide drug determination in pharmaceutical and biological urine samples using a novel continuous flow-injection analysis technique that is rapid, simple, economical, and sensitive. The complex formed by the reaction of hydrochlorothiazide and O-phenylenediamine with potassium ferricyanide to produce an orange-colored product at 480 nm was the basis for the proposed method. Other chemical and physical parameters that affect the stability and development of the colored product used in this developed method includes sample volume, flow rate, reagent concentrations, and reaction coil. The proposed method’s linearity ranges from 5 to 150 μg.mL-1 and its correlation coefficients were 0.9988, and the recovery percentage and error percentage were 100.88 and 0.88, respectively. The detection limit and Limit of quantification values were 2.622 and 7.97. A sample throughput of 90 samples. hour1- . The new approach was effectively employed to determine the presence of hydrochlorothiazide in the pure, biological, and pharmaceutical samples.